Susceptibility to DNA damage caused by abrogation of Rad54 homolog B: A putative mechanism for chemically induced cleft palate. (30th May 2021) - Qiao, Weiwei; Huang, Pei; Wang, Xinhuan; Meng, Liuyan
Abstract: Exposure to environmental toxicants such as all-trans retinoic acid (atRA) and 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin (TCDD) may cause cleft palate (CP), which process is related to DNA damage. Rad54B, an important DNA damage repaired protein, has been proved to be associated with non-syndromic cleft lip with palate (NSCLP). In the present study, we sought to clarify the role of Rad54B in palatal development and environment-induced CP. atRA (100 mg/kg) and TCDD (40 μg/kg) were used to induce CP in mice (C57BL/6 J mice). In this study, mouse embryonic heads were collected on embryonic day (E) 13.5∼16.5. The expression level of DNA repair protein Rad54 homolog B (Rad54B) was significantly decreased while those of the DNA double-strand breaks (DSBs) marker γ-H2A.X, apoptosis marker caspase-3 and p53 were significantly increased in the palatal shelves upon exposure to atRA and TCDD relative to the control. Primary mouse embryonic palatal mesenchymal cells (MEPMs) were cultured and transfected with siRNA or adenovirus in vitro to knock down or increase the level of Rad54B. Rad54B knockdown resulted in increased cellular S-phase arrest and apoptosis as well as decreased cell proliferation. Rad54B overexpression also increased apoptosis and reduced cell proliferation. Western blotting was used to detect the level of γ-H2A.X in transfected cells stimulated with etoposide (ETO, a DSBs inducer), and after 5 μM ETO stimulation of transfected MEPMs, the expression of γ-H2A.X was increased in Rad54B-knockdown cells. The expression of Mdm2, Mdmx and p53 with changes in Rad54B was also detected and coimmunoprecipitation was performed to analyze the combination of Mdm2 and p53 when Rad54B was changed in MEPMs. Knockdown of Rad54B inhibited the expression of Mdm2 and Mdmx, while the level of p53 increased. The coimmunoprecipitation results showed a decreased combination of Mdm2 and p53 when Rad54B was knocked down. Therefore, Rad54B can regulate the cell cycle, proliferation, and apoptosis of MEPMs. The loss of Rad54B increased the sensitivity of MEPMs to DSBs inducers, promoted apoptosis, and suppressed the proliferation of MEPMs by inhibiting the degradation of p53. Taken together, these findings suggest that Rad54B may play a key regulatory role in environment-induced CP.